Metabolic regulation by biomaterials in osteoblast - Kang, Zhengyang; Wu, Bin; Zhang, Luhui; Liang, Xinzhi; Guo, Dong; Yuan, Shuai; Xie, Denghui (Frontiers in Bioengineering and Biotechnology, 2023)
The repair of bone defects caused by high-energy injury, infection, or pathological fracture continues to pose a significant challenge in the medical field. The development of metabolic regulation materials, also known as "biomaterials inspired by metabolic regulation, provides a promising solution to this problem and has emerged as a prominent research area in regenerative engineering. Despite recent advances in cell metabolism research that have deepened our understanding of metabolic regulation in bone regeneration, our current understanding of whether intracellular metabolic pathways are affected by materials remains limited. This review provides an overview of the mechanisms of bone regeneration, a detailed discussion of metabolic regulation in bone regeneration in osteoblasts and metabolic regulation materials for bone regeneration. Furthermore, it introduces how materials, such as promoting favorable physicochemical characteristics (e.g., bioactivity, appropriate porosity, and superior mechanical properties), incorporating external stimuli (e.g., photothermal, electrical, and magnetic stimulation), and delivering metabolic regulators (e.g., metal ions, bioactive molecules like drugs and peptides, and regulatory metabolites such as alpha-ketoglutarate), can impact cell metabolism and lead to regulation of cell behavior. Considering the growing interest in cell metabolic regulation, advanced materials have the potential to aid a larger population in overcoming bone defects.